Can “the expanded free maternity services” enable Kenya to achieve universal health coverage by 2030: qualitative study on experiences of mothers and healthcare providers - Ombere, Stephen Okumu (Frontiers in Health Services, 2024)
IntroductionUniversal health coverage is a global agenda within the sustainable development goals. While nations are attempting to pursue this agenda, the pathways to its realization vary across countries in relation to service, quality, financial accessibility, and equity. Kenya is no exception and has embarked on an initiative, including universal coverage of maternal health services to mitigate maternal morbidity and mortality rates. The implementation of expanded free maternity services, known as the Linda Mama (Taking Care of the Mother) targets pregnant women, newborns, and infants by providing cost-free maternal healthcare services. However, the efficacy of the Linda Mama (LM) initiative remains uncertain. This article therefore explores whether LM could enable Kenya to achieve UHC.MethodsThis descriptive qualitative study employs in-depth interviews, focus group discussions, informal conversations, and participant observation conducted in Kilifi County, Kenya, with mothers and healthcare providers.Results and discussionThe findings suggest that Linda Mama has resulted in increased rates of skilled care births, improved maternal healthcare outcomes, and the introduction of comprehensive maternal and child health training for healthcare professionals, thereby enhancing quality of care. Nonetheless, challenges persist, including discrepancies and shortages in human resources, supplies, and infrastructure and the politicization of healthcare both locally and globally. Despite these challenges, the expanding reach of Linda Mama offers promise for better maternal health. Finally, continuous sensitization efforts are essential to foster trust in Linda Mama and facilitate progress toward universal health coverage in Kenya.